2020
DOI: 10.1161/hypertensionaha.119.14149
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Patterns and Target Organ Damage in Adolescents With Ambulatory Prehypertension

Abstract: Although the importance of office prehypertension/high normal blood pressure (BP) has been well documented, the significance of ambulatory prehypertension (AmbPreHT) has not been determined. We analyzed markers of target organ damage and hemodynamics in adolescents with AmbPreHT in comparison with hypertensive and normotensive subjects. Out of 304 white patients aged 15.0±2.5 years with office hypertension, 30 children had AmbPreHT and were compared with 66 normotensive healthy children and 92 children with tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 43 publications
3
29
0
2
Order By: Relevance
“…However, average BMI in adolescents with blood pressure above the 90th percentile was at the 86th percentile. Similarly, in our study, 29% of adolescents with PH were obese and 53% were overweight [29]. Analysis of body composition with the use of dual X-ray densitometry (DXA) showed that the relation between adipose mass and lean body mass is disturbed in hypertensive adolescents [30].…”
Section: Body Compositionsupporting
confidence: 69%
“…However, average BMI in adolescents with blood pressure above the 90th percentile was at the 86th percentile. Similarly, in our study, 29% of adolescents with PH were obese and 53% were overweight [29]. Analysis of body composition with the use of dual X-ray densitometry (DXA) showed that the relation between adipose mass and lean body mass is disturbed in hypertensive adolescents [30].…”
Section: Body Compositionsupporting
confidence: 69%
“…As reported previously, patients with ISH and normal cSBP had lower prevalence of LVH and lower values of cIMT and PWV than those with elevated cSBP [9]. The finding of mild forms of TOD in subjects with brachial hypertension and normal cSBP is not surprising because cIMT and LVMi increase with change of blood pressure status from normotension to severe ambulatory hypertension and cSBP was found to be one of the predictors of LVMi [30]. Although subjects included in our study had normal cSBP values, they were above median values [17].…”
Section: Discussionsupporting
confidence: 72%
“…Z-cIMT was positively associated with Z-BMI, an association that was maintained after adjusting for age, sex, and cardiovascular risk factors ( 30 ). Another recent paper on children found that 24-h systolic BP, but not cSBP, is linked to Z-cIMT in the multivariate regression analysis ( 31 ). The same study found an association between cSBP and LVH in children similar to the data coming from Litwin and colleagues ( 32 ), but again the subject included in the studies were hypertensive children.…”
Section: Discussionmentioning
confidence: 99%